PENGARUH GOOD CORPORATE GOVERNANCE, LEVERAGE, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP KUALITAS LABA (Studi pada Perusahaan Publik yang Termasuk Dalam Pemeringkatan CGPI Tahun 2013-2016) - Silviya Yenni Marsela; Maryono Maryono (Dinamika Akuntansi Keuangan dan Perbankan, 2017)
The purpose of this research is to examine and analyze the influence of good corporate governance, Leverage, profitability and company size to earnings quality. The population is the entire company included in the CGPI ranking for the period of 2013-2016. Sampling technique using purposive sampling. The sample criteria in this study are (a) Companies that follow CGPI ranking in 2012-2016. (b) Companies listed on the Stock Exchange (c) The Company earns a positive profit. Analyzer used is multiple linear regression. The results of the analysis can be concluded that: Good corporate governance positive effect on earnings quality. Leverage has no effect on earnings quality. Profitability has no effect on earnings quality. Company size has a positive effect on earnings quality. Keywords: good corporate governance, leverage, profitability, firm size and earnings quality